Nutritional Status Among Workers: Impact, Interventions, and Global Implications: A Systematic Review - Fadillah Ulva; Delmi Sulastri (Jurnal Ners, 2025)
The nutritional status of workers significantly influences occupational health, with both undernutrition and overnutrition posing substantial global challenges. Among the employed population, poor dietary practices, food scarcity, and strenuous work circumstances contribute to anemia, obesity, and various other health complications. This systematic review aim is to aggregate data on employee nutritional status, identify effective workplace interventions, and examine the global implications of worker nutrition on public health and productivity. A comprehensive literature search was conducted by PubMed, ScienceDirect, and Google Scholar with PRISMA guidelines. Papers examining dietary trends, nutritional status, and health impacts among workers published from 2015 to 2024 were included. After screening and comprehensive evaluation, ten studies met the inclusion criteria. The findings reveal a dual burden of malnutrition among employees: a significant prevalence of anemia among women and manual laborers, alongside rising rates of overweight and obesity among sedentary and night shift workers. Food insecurity and substandard nutrition quality were widespread among low-income and migrant workers. Despite long-term design and sustainability challenges, worksite nutrition interventions and educational programs demonstrated potential in altering workers' health outcomes. Employee nutrition is essential for sustaining health, enhancing productivity, and reducing health inequities. Multisectoral measures, such as modifications to the work environment, nutritional education, and the provision of healthy office lunches, are recommended. The cultivation of a productive and healthy global workforce hinges on the prioritization of public health issues, particularly the imperative to address workers' nutrition